The Creativity Skills of Auditory, Visual, and Kinesthetic Learners in Solving Cube and Cuboid Problems - Zakiatus Qurrotul A'yun; Dwi Juniati; Ismail Ismail (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika (JRPIPM), 2021)
study aims to describe the creativity skills of Junior High School students in solving cube and cuboid problems based on student learning styles. The research instruments used were creativity skills tests, a learning style questionnaire, and interviews. As many as three seventh graders who have different learning styles: visual, auditory, and kinesthetic, working on a cuboid/cube problem. Their performances on such a problem were then assessed regarding fluency, flexibility, and novelty. The results showed that the visual learner produced two different solutions with two different methods/strategies and completed his solution by providing a lot of illustrations/representations although they could not be categorized as novelty solutions. Meanwhile, the auditory learner provided two different solutions with two different methods/strategies. More particularly, he determined the appropriate size and found a suitable size by using a three-variable linear equation for the cube and cuboid problem although he produced some mistakes and uncompleted on the work procedures. Lastly, the kinesthetic learner provided two different solutions with one method/strategy, such as by directly determining the various correct sizes for the problem-solution although the answers could not be categorized novelty for creativity skill. Further studies are suggested to involve more participants to get a wider insight on the students creativity for different learning styles.